Evaluation of chromosomal aberrations induced by 188Re-dendrimer nanosystem on B16f1 melanoma cells. (31st May 2018) - Tassano, Marcos; Oddone, Natalia; Fernández, Marcelo; Porcal, Williams; García, María Fernanda; Martínez-López, Wilner; Benech, Juan Claudio; Cabral, Pablo
Abstract: Purpose: To study the rhenium-188 labeling of polyamidoamine (PAMAM) generation 4 (G4) dendrimer and its evaluation on biodistribution and chromosomal aberrations in melanoma cells induced by ionizing radiation as potential treatment agent. Materials and methods: Dendrimers were first conjugated with Suc-HYNIC (succinimidyl 6-hydrazinopyridine-3-carboxylic acid hydrochloride). Dendrimer-HYNIC was then incubated with 188 ReO4 − . Biodistribution was performed administrating 188 Re-dendrimer to normal (NM) or melanoma-bearing mice (MBM). Chromosome aberration test was conducted in order to measure treatment capacity of 188 Re-dendrimer in melanoma cells. Results: Radiolabeling yield of dendrimer was approx. 70%. Biodistribution studies in NM showed blood clearance with hepatic and renal depuration. MBM showed a similar pattern of biodistribution with tumor uptake of 6% of injected dose. Aberrant metaphases quantified in control cells were 7%, increasing to 29.5% in cells treated with 15 μ Ci (0.555 MBq) of 188 Re-dendrimer for 24 h. Conclusions: 188 Re-dendrimer can produce double-stranded breaks in DNA induced by ionizing radiation in melanoma cells in vitro.